Rare Co-occurrence of Ocular Myasthenia Gravis in Hyperthyroidism: A Case Report - Kandel, Sanjog; Chaudhary, Shatdal; Jaiswal, Niraj Kumar; Dhakal, Pushpa Raj; Shahi, Aakash; Karki, Manoj (Journal of Universal College of Medical Sciences, 2023)
A rare clinical presentation of ocular myasthenia gravis (OMG) with thyroid disorders, has been reported and documented in the past. There is similarity in the presentation of patients with OMG and thyroid opthalmopathy as a complication of thyrotoxi- cosis. The tendency of myasthenia gravis to get overlooked as separate entity despite having thyrotoxic presentation con-comit- tantly necessitates knowledge, thorough examination, and an experienced approach, to aid in its diagnosis. We have discussed two cases in a thyrotoxic state, with symptoms of ocular myasthenia gravis and clinical approach in our setting.